A Distributed Convex Optimization Algorithm over Directed Networks with Time Delay - Wei, Yutian; Xie, Jin; Gao, Weifeng; Li, Hong (Chinese Control Conference, 2024)
This paper aims to explore a novel distributed convex optimization algorithm over directed networks with communication delay based on zero-gradient-sum strategy to solve a class of the distributed convex optimization problem. Firstly, distributed convex optimization problem is formulated as minimizing a separable global objective function. Secondly, the convergence of improved algorithm is analyzed by constructing a Lyapunov-Krasovskii functional. In addition, a time delay upper bound is derived to make sure that all agents cooperatively converge to the global optimal consistency as a sufficient condition. Finally, a numerical simulation example is given to verify the effectiveness of improved algorithm.